Economic burden of attention-deficit/hyperactivity disorder among children and adolescents in the United States: a societal perspective. (31st December 2022) - Schein, Jeff; Adler, Lenard A.; Childress, Ann; Cloutier, Martin; Gagnon-Sanschagrin, Patrick; Davidson, Mikhaïl; Kinkead, Frédéric; Guerin, Annie; Lefebvre, Patrick
Abstract: Objective: To provide a comprehensive evaluation of the economic burden associated with attention-deficit/hyperactivity disorder (ADHD) among children and adolescents from a US societal perspective. Materials and methods: Direct healthcare costs of children (5–11 years) and adolescents (12–17 years) with ADHD were obtained using claims data from the IBM MarketScan Research Databases (01/01/2017–12/31/2018). Direct non-healthcare and indirect costs were estimated based on literature and government publications. Each cost component was estimated using a prevalence-based approach, with per-patient costs extrapolated to the national level. Results: The total annual societal excess costs associated with ADHD were estimated at 19.4 billion among children (6, 799 per child) and 13.8 billion among adolescents (8, 349 per adolescent). Education costs contributed to approximately half of the total excess costs in both populations (11.6 billion [59.9%] in children; 6.7 billion [48.8%] in adolescents). Other major contributors to the overall burden were direct healthcare costs (5.0 billion [25.9%] in children; 4.0 billion [29.0%] in adolescents) and caregiving costs (2.7 billion [14.1%] in children; 1.6 billion [11.5%] in adolescents). Limitations: Cost estimates were calculated based on available literature and/or governmental publications due to the absence of a single data source for all costs associated with ADHD. Thus, the quality of cost estimates is limited by the accuracy of available data as well as the study populations and methodologies used by different studies. Conclusion: ADHD in children and adolescents is associated with a substantial economic burden that is largely driven by education costs, followed by direct healthcare costs and caregiver costs. Improved intervention strategies and policies may reduce the clinical and economic burden of ADHD in these populations.